Community Beliefs About Intentional Injury and Responsibility for Prevention. (March 2015) - Too, Lay San; Haworth, Narelle; Lennon, Alexia; Titchener, Kirsteen
Community beliefs related to intentional injury inflicted by others were examined in a population-based telephone survey (n = 1032) in Queensland, Australia. Young adults 18 to 24 years old were nominated as the most likely to be intentionally injured. It was found that 89.1% of respondents nominating this group believed that the injury incidents occur in alcohol environments. Though respondents from this age group also identified 18- to 24-year-olds as most likely to be intentionally injured, this was at a significantly lower level when compared with parents or 25- to 64-year-olds respondents. Responsibility for preventing injuries was placed on proprietors of licensed premises, schools, and parents/family of the victim for alcohol, school, and home environments, respectively. Beliefs were aligned with prevalence data on intentional injury, demonstrating a high level of awareness in the community about likely victims and situations where intentional injuries occur. Interventions could target families of young adults to capitalize on high levels of awareness about young adult vulnerability.